2011
DOI: 10.1093/molbev/msr094
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Protein Conformational Changes Revealed by a Network of Evolutionarily Coupled Residues

Abstract: An improved understanding of protein conformational changes has broad implications for elucidating the mechanisms of various biological processes and for the design of protein engineering experiments. Understanding rearrangements of residue interactions is a key component in the challenge of describing structural transitions. Evolutionary properties of protein sequences and structures are extensively studied; however, evolution of protein motions, especially with respect to interaction rearrangements, has yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 78 publications
5
32
0
Order By: Relevance
“…While high pMI sites in the Hsp70 structures corresponded mostly to structurally stable residues, coevolving positions exhibited a wide range of conformational mobility with the peaks pointing to the middle part of the spectrum. These findings corroborated with evolutionary studies of protein dynamics [110,111] suggesting that highly coevolving residues may preferentially occupy regions of intermediate mobility. We argue that conformational variability of highly coevolving residues that surround rigid regulatory sites may enable concerted rearrangements of specific interactions associated with global allosteric changes.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…While high pMI sites in the Hsp70 structures corresponded mostly to structurally stable residues, coevolving positions exhibited a wide range of conformational mobility with the peaks pointing to the middle part of the spectrum. These findings corroborated with evolutionary studies of protein dynamics [110,111] suggesting that highly coevolving residues may preferentially occupy regions of intermediate mobility. We argue that conformational variability of highly coevolving residues that surround rigid regulatory sites may enable concerted rearrangements of specific interactions associated with global allosteric changes.…”
Section: Resultssupporting
confidence: 86%
“…However, the vast majority of residues with high cMI scores tend to occupy flexible regions, primarily in the subdomain II of the NBD and the substrate binding region ( Fig 5C and 5D ). These observations corroborated with the notion that coevolving flexible residues undergoing cooperative structural changes may constitute recognition elements of substrate binding sites [110,111] . Another group of regulatory Hsp70 residues (D326, K414, N415, Q442 and D481) revealed high cMI scores and intermediate mobility level ( Figs 4 and 5 ).…”
Section: Resultssupporting
confidence: 80%
“…These findings suggested that coevolutionary networks may form direct pathways for transmitting allosteric signals [ 100 ]. The most probable path in the Dabrafenib-BRAF complex (85% occupancy) could proceed from F595 of monomer A to the R-spine residues of the αC-helix (V504, L505), subsequently reaching to the interfacial residue R509 of the monomer A ( Fig 12B ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, coevolving residues are often located close to each other in the protein structure [ 96,97 ] and may form independent structural modules (or protein sectors) with distinct biochemical functions [ 8890,98,99 ]. Functional conformational changes could be often enabled through networks of evolutionarily coupled residues [ 100 ].…”
Section: Introductionmentioning
confidence: 99%
“…• Combination of evolutionary conservation data has proven to be an efficient predictor of intra-protein signaling pathways [60,85,[210][211][212]. Similar approaches may be extended to protein neighborhoods helping to find starting sites for allo-network drug action.…”
Section: Possible Methods To Identify Allo-network Drug Targetsmentioning
confidence: 99%